Hyaluronic Acid–Povidone-Iodine Compound Facilitates Diabetic Wound Healing in a Streptozotocin-Induced Diabetes Rodent Model. Issue 5 (May 2019) - Chen, Rong-Fu; Wang, Chun-Ting; Chen, Yu-Hua; Chien, Ching-Ming; Lin, Sin-Daw; Lai, Chung-Sheng; Wang, Ching-Jen; Kuo, Yur-Ren
Abstract : Background: This study investigated whether a hyaluronic acid–povidone-iodine compound can enhance diabetic wound healing. Methods: A dorsal skin defect (6 × 5 cm) in a streptozotocin-induced diabetes rodent model was used. Seventy male Wistar rats were divided into seven groups: I, normal control; II, diabetic control, no treatment; III, diabetic rats, lower molecular weight (100 kDa) hyaluronic acid; IV, rats, higher molecular weight (1000 kDa) hyaluronic acid; V, rats, 0.1% povidone-iodine; VI, rats, lower molecular weight hyaluronic acid plus povidone-iodine; and VII, rats, higher molecular weight hyaluronic acid plus povidone-iodine. Histologic examination was performed with hematoxylin and eosin staining. CD45, Ki-67, prolyl 4-hydroxylase, and vascular endothelial growth factor were evaluated with immunohistochemical staining. Results: Compared with the control, higher molecular weight hyaluronic acid plus povidone-iodine–treated rats had significantly reduced wound area ( p < 0.001). Higher molecular weight hyaluronic acid plus povidone-iodine increased wound healing time when compared with higher molecular weight hyaluronic acid, povidone-iodine, or lower molecular weight hyaluronic acid plus povidone-iodine. Histology revealed significantly increased neovessels and suppressed inflammatory response in the higher molecular weight hyaluronic acid plus povidone-iodine group when compared with the control group. Immunohistochemical staining revealed significantly increased Ki67, prolyl 4-hydroxylase, and vascular endothelial growth factor expression, and suppressed CD45 expression in the higher molecular weight hyaluronic acid plus povidone-iodine group when compared with the other groups. Conclusion: Higher molecular weight hyaluronic acid plus povidone-iodine complex dressing significantly facilitated diabetic wound healing via increasing neovascularization and tissue regeneration and suppressing a proinflammatory response. Abstract : Supplemental Digital Content is available in the text.